2017
DOI: 10.1172/jci89401
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens enhance myoblast differentiation in facioscapulohumeral muscular dystrophy by antagonizing DUX4 activity

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant neuromuscular disorder that is characterized by extreme variability in symptoms, with females being less severely affected than males and presenting a higher proportion of asymptomatic carriers. The sex-related factors involved in the disease are not known. Here, we have utilized myoblasts isolated from FSHD patients (FSHD myoblasts) to investigate the effect of estrogens on muscle properties. Our results demonstrated that estrogens counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…In the current study we found no influence of sex on disease severity. Possible protective effects of antioxidants and female reproductive hormones are still under active investigation, but results are contradictory . One study on aerobic exercise in FSHD showed that it slows down disease progression in leg muscles …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study we found no influence of sex on disease severity. Possible protective effects of antioxidants and female reproductive hormones are still under active investigation, but results are contradictory . One study on aerobic exercise in FSHD showed that it slows down disease progression in leg muscles …”
Section: Discussionsupporting
confidence: 91%
“…This study showed that the D4Z4 repeat array size (mainly) in the range from 5 to 9 repeat are contradictory. [28][29][30] One study on aerobic exercise in FSHD showed that it slows down disease progression in leg muscles. 31 The characteristic pattern of muscle involvement in FSHD prompted us to assess whether the influence of genetic and epigenetic factors differs per body region or muscle group.…”
Section: Discussionmentioning
confidence: 99%
“…On a molecular basis, a gender effect on methylation levels was not seen [15]. A recent study proposed an estrogen receptor as a potential disease modifier by interfering with DUX4 transcriptional activity [51], but further studies are necessary to investigate gender-specific disease effects.…”
Section: Disease Progressionmentioning
confidence: 98%
“…Sex differences in disease severity in FSHD patients have been observed in different studies, consistently reporting a higher proportion of women among asymptomatic gene carriers [5][6][7][8][9]. Additionally, cases have been reported of women experiencing a persistent worsening of symptoms following pregnancies, early menopause or anti-estrogenic therapy [10][11][12]. However, limited work has been done to systematically assess changes in disease progression during periods of pronounced hormonal changes.…”
Section: Introductionmentioning
confidence: 99%